2006
DOI: 10.1021/bm060007u
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation in Ultrahigh Molecular Weight Polyethylene and Cross-Linked Polyethylene Acetabular Cups Tested against Roughened Femoral Heads in a Hip Joint Simulator

Abstract: This study was aimed at comparing the oxidative degradation of commercial acetabular cups made of cross-linked polyethylene (XLPE) and conventional ultrahigh molecular weight polyethylene (UHMWPE). After testing against deliberately scratched CoCrMo femoral heads in a hip joint simulator, the cups, microtomed parallel to the articulating surface, were analyzed by IR spectroscopy. Due to the potential for artifacts caused by absorbed contaminants, the IR spectra were compared only after hexane extraction; actua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 63 publications
0
39
0
Order By: Relevance
“…Even though UHMWPE oxidation has been described by several groups [3,4,9,12] we originally reported that the oxidize alkane polymers, within 10 to 16 carbon atoms are by far more immunogenic in TLR1/2 stimulation that the non oxidize counterpart [5]. Herein we complement the previous data with further experiments indicating that TLR1/2 engagement induces a pro-inflammatory transcription program mediated by NFkB signaling pathways, inducing the expression of pro-IL-1β and pro-IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…Even though UHMWPE oxidation has been described by several groups [3,4,9,12] we originally reported that the oxidize alkane polymers, within 10 to 16 carbon atoms are by far more immunogenic in TLR1/2 stimulation that the non oxidize counterpart [5]. Herein we complement the previous data with further experiments indicating that TLR1/2 engagement induces a pro-inflammatory transcription program mediated by NFkB signaling pathways, inducing the expression of pro-IL-1β and pro-IL-18.…”
Section: Discussionmentioning
confidence: 99%
“…The general recommended application temperature for PP products is below 80°C. On the other hand, the polymer network is known to increase product mechanical strength, temperature stability, and resistance to solvents, creep, and stress-cracking [24][25][26][27][28]. Cross linked polyethylene (x-PE) is used everywhere today in water piping and high voltage electrical cables [29].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, studies have often shown that some mechanical properties (impact toughness in particular) are compromised [3][4][5][6][7][8]. Current research efforts are being directed towards reducing the wear rate of UHMWPE without sacrificing the impact toughness typically associated with crosslinking.…”
Section: Introductionmentioning
confidence: 99%